Positive electrode material precursor and preparation method thereof, positive electrode material, battery and power-related equipment
By designing the precursor of the hydroxide positive electrode material containing transition metal elements and optimizing its morphology and structure, the problem of difficult to take into account both the crushing resistance and circulation performance of the positive electrode material is solved, and higher battery circulation performance and electrochemical capacity are achieved.
Patent Information
- Application Number
- CN202411852212.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
The existing cathode materials have problems such as poor crush resistance and difficulty in taking into account both the cycle performance and electrochemical capacity.
By designing a precursor of hydroxide positive electrode material containing transition metal elements, its morphology and structure are optimized so that the particle size D50 and the mean value of primary particles on the surface of secondary particles meet the relationship formula (D50) 3/V=600-1400, thereby improving the internal structural compactness of the positive electrode material and lithium ion conduction efficiency.
It improves the anti-breakability and stability of the positive electrode material, and enhances the balance of the cycling performance and electrochemical capacity of the battery.
Smart Images

Figure CN119683706A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a positive electrode material precursor and a preparation method thereof, a positive electrode material, a battery and electrical equipment. Background Art
[0002] The positive electrode material precursor is the front-end material of the positive electrode material in the lithium battery, and plays a decisive role in the performance of the positive electrode material. The positive electrode material precursor is mainly hydroxide or carbonate containing transition metal elements such as nickel and cobalt, which is made into positive electrode material by sintering.
[0003] According to different battery application requirements, the cathode material precursor can be designed with different components so that the battery made of the prepared cathode material exhibits different performance characteristics such as high energy density, high cycle life and high thermal stability. However, due to the morphology and structure of the cathode material precursor, the cathode material still has the defect of poor resistance to crushing, and the internal structure of the cathode material is easily damaged by the insertion / deinsertion of lithium ions during the charge and discharge cycle, resulting in the inability to achieve a limited balance between the battery's cycle performance and electrochemical capacity.
[0004] In view of the above, the present invention is proposed. Summary of the invention
[0005] The present application provides a positive electrode material precursor and a preparation method thereof, a positive electrode material, a battery and electrical equipment, aiming to solve the above-mentioned problems or at least alleviate the defects existing in the above-mentioned prior art.
[0006] In a first aspect, the present application provides a positive electrode material precursor, wherein the positive electrode material precursor is a hydroxide containing a transition metal element; the positive electrode material precursor comprises secondary particles composed of a plurality of primary particles, and the particle size D50 of the positive electrode material precursor and the primary particle volume mean V on the surface of the secondary particles satisfy the relationship: (D50) 3 / V=600~1400.
[0007] The cathode material precursor provided in the present application is a transition metal hydroxide. Through the morphology optimization design of the cathode material precursor, the cathode material precursor includes secondary particles composed of multiple primary particles. The particle size D50 of the cathode material precursor and the primary particle volume mean V on the surface of the secondary particles satisfy the relationship: (D50) 3 / V=600~1400, which means that compared with the traditional positive electrode material precursor, under the same secondary particle size, the primary particles on the surface of the secondary particles of the positive electrode material precursor of the present application have a larger volume, and the number of primary particles on the surface of a single secondary particle is smaller, which is beneficial for the positive electrode material precursor to obtain a denser internal structure of the positive electrode material, the positive electrode material can have a lower specific surface area, and the number of grain boundaries in the crystal structure of the positive electrode material can be reduced, so as to improve the anti-crushing property of the positive electrode material, inhibit the damage of the internal structure of the positive electrode material during the charge and discharge cycle, thereby improving the stability of the positive electrode material and ensuring the cycle performance of the battery; and, the primary particles on the surface of the secondary particles have a larger volume, and the primary particles on the surface of the secondary particles can have more basic building blocks, so as to improve the conduction efficiency of lithium ion deintercalation and diffusion during the charge and discharge process of the positive electrode material, so that the positive electrode material can have higher electrochemical performance, and effectively balance the battery cycle performance and electrochemical capacity.
[0008] In some embodiments, the cathode material precursor satisfies at least one of the following conditions:
[0009] (1) (D50) 3 / V=800~1200;
[0010] (2) The particle size D50 of the positive electrode material precursor is 5.00 to 8.00 μm, preferably 6.00 to 7.00 μm;
[0011] (3) The average volume V of the primary particles on the secondary particle surface is 0.250 to 0.550 μm 3 , preferably 0.320~0.450μm 3 ;
[0012] (4) The primary particle comprises a plurality of thin sheet units, and the number of thin sheet units of a single primary particle is 25 to 60, preferably 40 to 50;
[0013] (5) The secondary particles include a core-shell structure consisting of a core and an outer shell, and the porosity of the core is greater than the porosity of the outer shell.
[0014] In some embodiments, the cathode material precursor satisfies at least one of the following conditions:
[0015] A. The specific surface area of the cathode material precursor is 1.00 to 5.00 m 2 / g, preferably 1.5 to 3.8 m 2 / g;
[0016] B. The sphericity R of the secondary particles is 86%≤R<100%;
[0017] C. The overall porosity of the secondary particles is 0.5-4.0%;
[0018] D. Multiple thin-sheet units of primary particles are stacked and arranged along the thickness direction;
[0019] E. The primary particles are in block or long strip shape;
[0020] F. The average length of the primary particles on the surface of the secondary particles is 0.710 to 0.830 μm; optionally, the average width of the primary particles on the surface of the secondary particles is 0.590 to 0.870 μm; optionally, the average thickness of the primary particles on the surface of the secondary particles is 0.510 to 0.810 μm;
[0021] G. The porosity of the inner core is 2-10%, and the porosity of the outer shell is 0.01-1%.
[0022] In some embodiments, the cathode material precursor is a nickel-containing hydroxide and satisfies at least one of the following conditions:
[0023] I. The molar content of nickel accounts for 50-70% of the molar content of the total metal elements;
[0024] J. The cathode material precursor is a hydroxide containing nickel, cobalt and manganese, and the molar content of manganese accounts for 10 to 30% of the molar content of the total metal elements;
[0025] K, the chemical formula of the cathode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.5≤x≤0.7, 0.1≤y≤0.3, 0.1≤z≤0.3, 0≤v≤0.015, and M is a doping element; optionally, 0.60<x<0.70, 0.10<y<0.25, 0.15<z<0.25, 0≤v≤0.015; optionally, M is at least one of Al, Ti, Zr, Mo, Cr, W, Mg, Ba, Nb or Sr.
[0026] The second aspect of the present application provides a method for preparing the above-mentioned positive electrode material precursor, comprising:
[0027] Preparing a metal salt solution, a precipitant solution and a complexing agent solution, and mixing the solvent, the precipitant solution and the complexing agent solution to obtain a base solution;
[0028] A metal salt solution, a precipitant solution and a complexing agent solution are introduced into the base liquid to perform a synthesis reaction in stages to obtain a hydroxide slurry;
[0029] After post-processing the hydroxide slurry, a positive electrode material precursor is obtained.
[0030] In some embodiments, the synthesis reaction includes a first synthesis stage, a second synthesis stage and a third synthesis stage which are performed sequentially, wherein:
[0031] In the first synthesis stage, the pH value of the reaction system is maintained unchanged during the first period of time after the synthesis reaction begins;
[0032] In the second synthesis stage, the pH value of the reaction system is controlled to gradually decrease to the first target pH value within the second time period, and then the reaction is continued for a third time period;
[0033] In the third synthesis stage, the pH value of the reaction system is controlled to remain unchanged, or to increase or decrease to the second target pH value within the fourth time period; and, in the third synthesis stage, the concentration of the complexing agent in the reaction system is controlled to remain unchanged, or to increase or decrease to the target concentration value within the fifth time period, and the reaction is continued; to obtain a hydroxide slurry;
[0034] The reaction time of the third synthesis stage is longer than that of the second synthesis stage, and the reaction time of the second synthesis stage is longer than that of the first synthesis stage.
[0035] In some embodiments, the preparation method selects one or more of the following conditions:
[0036] a. Post-treatment includes washing, centrifuging, drying and screening to remove magnetism of the hydroxide slurry in sequence;
[0037] b. The synthesis reaction is carried out in a reactor, and before the third synthesis stage, the materials after the reaction in the second synthesis stage are separated into separate reactors;
[0038] c. During the process of controlling the pH value of the reaction system to decrease in the second time period, the pH value of the reaction system decreases by 0.10 to 0.20 every 1 to 2 hours; optionally, during the process of controlling the pH value of the reaction system to increase or decrease in the fourth time period, the pH value of the reaction system increases or decreases by 0.10 to 0.20 every 1 to 2 hours;
[0039] d. Control the concentration of the complexing agent in the reaction system to increase or decrease during the fifth time period, so that the concentration of the complexing agent in the reaction system increases or decreases by 0.4 to 0.6 g / L every 1 to 2 hours;
[0040] e. The first target pH value is 11.20 to 11.60;
[0041] f. When the pH value of the reaction system is controlled to rise in the fourth time period, the second target pH value is 11.00 to 11.40; or, when the pH value of the reaction system is controlled to fall in the fourth time period, the second target pH value is 11.40 to 11.80;
[0042] g. When the concentration of the complexing agent in the reaction system is controlled to increase in the fifth time period, the target concentration value is 5.0 g / L to 7.5 g / L; or, when the concentration of the complexing agent in the reaction system is controlled to decrease in the fifth time period, the target concentration value is 7.5 g / L to 9.0 g / L;
[0043] h, the first time period is 1 to 2 hours; optionally, the second time period or the fourth time period is 4 to 12 hours; optionally, the third time period is 25 to 30 hours; optionally, the fifth time period is 4 to 8 hours;
[0044] i. The total reaction time of the synthesis reaction is 70 to 130 hours;
[0045] j. During the synthesis reaction, the feed rate of the metal salt solution is 4-6% / h of the reaction vessel volume;
[0046] k. During the synthesis reaction, the feed rate of the precipitant solution is 1.5-3.5% / h of the reaction vessel volume;
[0047] 1. During the synthesis reaction, the feeding rate of the complexing agent solution is 0.20-0.60% / h of the reaction vessel volume;
[0048] m. The reaction temperature of the synthesis reaction is 40 to 60°C, preferably 45 to 55°C;
[0049] n. The total metal molar amount of the metal salt solution is 1.5-2.5 mol / L;
[0050] o. The solute mass fraction of the precipitant solution is 30-34wt%;
[0051] p. The solute mass fraction of the complexing agent solution is 20-26wt%;
[0052] q. The pH value of the base solution is 11.60-12.00;
[0053] r. The complexing agent concentration of the base solution is 6.4-8.0 g / L;
[0054] s. The precipitant solution includes a sodium hydroxide solution;
[0055] t. The complexing agent solution includes aqueous ammonia.
[0056] A third aspect of the present application provides a positive electrode material, wherein the raw material of the positive electrode material includes the positive electrode material precursor as described above or the positive electrode material precursor prepared by the preparation method.
[0057] A fourth aspect of the present application provides a battery, the battery comprising an electrode made of the positive electrode material as described above.
[0058] A fifth aspect of the present application provides an electrical device, comprising the battery as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0060] Figure 1 This is a SEM image of the positive electrode material precursor prepared in Example 1 of the present application (magnification 10000 times);
[0061] Figure 2 CP diagram of the cathode material precursor prepared in Example 1 of the present application (magnification 10000 times);
[0062] Figure 3 This is a SEM image of the cathode material precursor prepared in Example 1 of the present application (magnification 200 times on the left, magnification 1000 times on the right);
[0063] Figure 4 This is a SEM image of the positive electrode material precursor prepared in Example 1 of the present application (the magnification of the left and right sides is 50,000 times);
[0064] Figure 5 This is a SEM image of the cathode material precursor prepared in Example 2 of the present application (magnification 10000 times);
[0065] Figure 6 This is a SEM image of the positive electrode material precursor prepared in Comparative Example 1 of the present application (magnification 10,000 times). DETAILED DESCRIPTION
[0066] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0067] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0068] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0069] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0070] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0071] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0072] In order to improve the defect that the positive electrode material still has poor anti-breakage property, and the internal structure of the positive electrode material is easily damaged by the insertion / deinsertion of lithium ions during the charge and discharge cycle, so that the cycle performance and electrochemical capacity of the battery cannot be taken into account to a limited extent, the embodiment of the present application provides a positive electrode material precursor, the positive electrode material precursor is a hydroxide containing a transition metal element; the positive electrode material precursor includes secondary particles composed of a plurality of primary particles, and the particle size D50 of the positive electrode material precursor and the primary particle volume mean V on the surface of the secondary particles satisfy the relationship: (D50) 3 / V=600~1400.
[0073] It can be understood that the primary particles of the positive electrode material precursor serve as the constituent units of the secondary particles. The larger the volume mean of the primary particles on the surface of the secondary particles, the fewer the number of primary particles carried on the surface of the secondary particles. In the above relationship, the ratio of the cube of the particle size D50 of the positive electrode material precursor to the volume mean V of the primary particles on the surface of the secondary particles is 600-1400, indicating that under the same secondary particle size, the primary particles on the surface of the secondary particles of the positive electrode material in the embodiment of the present application have a larger volume, and the number of primary particles on the surface of the secondary particles is smaller. The prepared positive electrode material has a higher resistance to crushing, thereby greatly reducing the internal structural damage caused by the insertion / deinsertion of lithium ions during the cyclic charge and discharge process, so as to improve the stability of the positive electrode material and ensure the cycle performance of the battery; moreover, the primary particles on the surface of the secondary particles have a larger volume, so that the primary particles on the surface of the secondary particles can have more basic constituent units, which is beneficial to improve the conduction efficiency of lithium ions during the insertion / deinsertion diffusion during the charge and discharge process of the positive electrode material, thereby improving the electrochemical performance of the positive electrode material and achieving a balance between the cycle performance and electrochemical capacity of the battery.
[0074] For example, the particle size D50 of the positive electrode material precursor in the embodiment of the present application and the primary particle volume average V on the secondary particle surface satisfy the relationship: (D50) 3 / V=600~1400, for example, (D50) 3 / V can be 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000, 1010, 1020, 1030, 1040, 1050 1290, 1300, 1310, 1320, 1330, 1340, 1350, 1360, 1370, 1380, 1390, 1400, or any value in the range of 600 to 1400.
[0075] In some embodiments, the particle size D50 of the positive electrode material precursor and the primary particle volume average V on the secondary particle surface satisfy the relationship: (D50) 3 / V=800~1200. The positive electrode material prepared by the positive electrode material precursor satisfying this relationship can have higher anti-crushing performance, so as to effectively balance the battery cycle performance and electrochemical capacity.
[0076] In some embodiments, the particle size D50 of the positive electrode material precursor is 5.00-8.00 μm, indicating that the particle size D50 of the positive electrode material precursor is relatively small. Under the condition of satisfying the above relationship, it is more conducive to reducing the specific surface area of the secondary particles, making the internal structure of the positive electrode material more compact and less prone to cracking during the cyclic charge and discharge process, thereby effectively taking into account the cycle performance and electrochemical capacity of the battery.
[0077] The particle size D50 of the positive electrode material precursor in the embodiment of the present application is 5.00-8.00 μm. For example, the particle size D50 of the positive electrode material precursor can be 5.00 μm, 5.10 μm, 5.20 μm, 5.30 μm, 5.40 μm, 5.50 μm, 5.60 μm, 5.70 μm, 5.80 μm, 5.90 μm, 6.00 μm, 6.10 μm, 6.20 μm, 6.30 μm, 6.40 μm, 6.50 μm, 6.60 μm, 6.70 μm, 6.80 μm, 6.90 μm, 7.00 μm, 7.10 μm, 7.20 μm, 7.30 μm, 7.40 μm, 7.50 μm, 7.60 μm, 7.70 μm, 7.80 μm, 7.90 μm, 8.00 μm, 8.10 μm, 8.20 μm, 8.30 μm, 8.40 μm, 8.50 μm, 8.60 μm, 8.70 μm, 8.80 μm, 8.90 μm, 9.00 μm, 9.10 μm, 9.20 μm, 9.30 μm, 9. The particle size D50 value can be 0μm, 6.40μm, 6.50μm, 6.60μm, 6.70μm, 6.80μm, 6.90μm, 7.00μm, 7.10μm, 7.20μm, 7.30μm, 7.40μm, 7.50μm, 7.60μm, 7.70μm, 7.80μm, 7.90μm, 8.00μm or any particle size D50 value in the range of 5.00 to 8.00μm.
[0078] In some embodiments, the particle size D50 of the cathode material precursor is preferably 6.00-7.00 μm. The particle size D50 of the cathode material precursor within this range is more conducive to reducing the specific surface area, making the internal structure of the cathode material more compact and more stable.
[0079] In some embodiments, the primary particle volume average V on the secondary particle surface is 0.250 to 0.550 μm 3 , which means that the single primary particle on the surface of the secondary particle has a larger volume, which is conducive to reducing the number of primary particles on the surface of the secondary particle, thereby making the internal structure of the positive electrode material obtained by the positive electrode material precursor denser, the positive electrode material can have a lower specific surface area, and the number of grain boundaries in the crystal structure of the positive electrode material can be reduced, so that the positive electrode material's resistance to crushing is improved.
[0080] In the embodiment of the present application, the average volume V of the primary particles on the surface of the secondary particles is 0.250-0.550 μm 3 For example, the average volume V of the primary particles on the secondary particle surface can be 0.250 μm 3 、0.275μm 3 , 0.300μm 3 , 0.325μm 3 、0.350μm 3 、0.375μm 3 , 0.400μm 3 , 0.425μm 3 、0.450μm 3 、0.475μm 3 , 0.500μm 3 、0.525μm 3 、0.550μm 3 or 0.250~0.550μm3 Any volume mean within the range.
[0081] In some embodiments, the average volume V of the primary particles on the surface of the secondary particles is preferably 0.320 to 0.450 μm. 3 Within this range, it is more conducive to reducing the number of primary particles on the surface of secondary particles, which makes the anti-crushing property of the positive electrode material more significantly improved.
[0082] In some embodiments, the primary particle includes a plurality of thin sheet units, and the number of thin sheet units of a single primary particle is 25-60.
[0083] It should be noted that the sheet unit in the embodiment of the present application refers to the basic constituent unit of the primary particle. The sheet unit has a relatively flat and thin structure, and the stacking or layered arrangement combination of multiple sheet units together constitutes a primary particle.
[0084] The number of thin film units of a single primary particle in the embodiment of the present application is 25 to 60. The number of thin film units on a single primary particle is relatively large, and the volume of the primary particle is relatively large. Under the condition of the same secondary particle size, it is more conducive to reducing the number of primary particles of the secondary particle, thereby reducing the number of grain boundaries of the positive electrode material, and promoting the improvement of the anti-crushing performance of the positive electrode material. In addition, the number of thin film units on a single primary particle is large, and the conduction efficiency is higher during the lithium ion insertion and extraction diffusion. The corresponding positive electrode material has more excellent electrochemical properties, which is more conducive to the effective consideration of the cycle performance and electrochemical capacity of the battery. For example, the number of thin film units of a single primary particle of the present application can be 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60 or any number within the range of 25 to 60.
[0085] In some embodiments, the number of thin film units of a single primary particle is preferably 40 to 50, which is more conducive to increasing the volume of a single primary particle, so as to make the number of primary particles of the secondary particles lower, thereby reducing the number of grain boundaries of the positive electrode material, and significantly improving the anti-crushing performance and electrochemical performance of the positive electrode material.
[0086] In some embodiments, multiple thin-sheet units of a primary particle are stacked in the thickness direction, and the multiple thin-sheet units are flat and thin in structure, and are stacked in the thickness direction to form a primary particle, which can form a tightly stacked primary particle structure, thereby promoting higher conduction efficiency and higher stability during the insertion and extraction and diffusion of lithium ions in the positive electrode material.
[0087] Generally, among the three dimensions (length, width, height) of a primary particle, length>width>thickness. If a primary particle has a plurality of stacked sheet units, the direction perpendicular to the stacking arrangement is defined as the thickness direction.
[0088] In some embodiments, the primary particles are in block or strip shape. The primary particles in this embodiment are in block shape, which means that the primary particles have a relatively compact, three-dimensional shape, without obvious long strip or flattened features, and the block-shaped primary particles are relatively balanced in size in all directions, without obvious extension or contraction; the primary particles in this embodiment are in strip shape, and the long strip-shaped primary particles have obvious extension characteristics in a certain direction, while the size in other directions is relatively small. This form makes the primary particles present an elongated shape, similar to a line or a rod. Multiple primary particles can be in block or strip shape, respectively. Compared with sheet-shaped primary particles, block or strip-shaped primary particles are more conducive to the increase of primary particle volume, and are conducive to reducing the number of primary particles on the surface of secondary particles. At the same time, the block or strip-shaped primary particles are more compact, which is conducive to improving the structural stability of the positive electrode material. However, when the number of primary particles is too small, it is not conducive to the use of the capacity of the positive electrode material.
[0089] In some embodiments, the average length size of the primary particles on the surface of the secondary particles is 0.710-0.830 μm; the average width size of the primary particles on the surface of the secondary particles is 0.590-0.870 μm; the average thickness size of the primary particles on the surface of the secondary particles is 0.510-0.810 μm; the length, width and length size of the primary particles on the surface of the secondary particles are larger, and have a higher volume share, so that the number of primary particles on the surface of the secondary particles can be reduced, which is beneficial to improve the anti-crushing performance of the positive electrode material, and promote the effective balance between the cycle performance and electrochemical capacity of the battery.
[0090] In some embodiments, the specific surface area of the cathode material precursor is 1.00 to 5.00 m 2 / g, preferably 1.5 to 3.8 m 2 / g; The specific surface area BET of the positive electrode material precursor is within this range, and the specific surface area of the positive electrode material precursor is low, which is conducive to the overall structure of the positive electrode material made therefrom being more compact, thereby reducing the contact points between the positive electrode material and the electrolyte, inhibiting the generation of side reactions with the electrolyte, and promoting the improvement of the cycle performance of the positive electrode material.
[0091] In some embodiments, the sphericity R of the secondary particles is 86%≤R<100%; the secondary particles of the positive electrode material precursor have a higher sphericity, which means that the primary particles on the surface of the secondary particles are evenly distributed, so that the surface of the positive electrode material has a higher flatness, which is beneficial to the positive electrode material made from the positive electrode material precursor. The stability is enhanced under high voltage, and the internal structure changes caused by the insertion / deinsertion of lithium ions during the cyclic charge and discharge process are reduced, thereby effectively reducing the operating power consumption of the battery and improving the safety of the battery.
[0092] Sphericity is an index of the roundness of the secondary particle's contour shape. The closer the secondary particle's shape is to a sphere, the closer the sphericity value is to 1 (100%). Sphericity = (4π×area) / (perimeter×perimeter). The calculation of sphericity is to use Avizo software to identify the perimeter and area of secondary particles in electron microscope images with a magnification of 1000 to 5000 times, and then calculate the sphericity of a single secondary particle. The sphericity of 5 to 10 secondary particles is randomly measured, and the average value is taken to calculate the sphericity of the material to be tested.
[0093] In some embodiments, the secondary particles include a core-shell structure consisting of a core and an outer shell, and the porosity of the core is greater than the porosity of the outer shell. The overall structure of the secondary particles of this embodiment is loose inside and tight outside, and the porosity of the core is greater than the porosity of the outer shell, so that the positive electrode material can have a higher structural stability, thereby effectively balancing the cycle performance and electrochemical capacity of the battery.
[0094] The CP image was analyzed using image analysis software (avizo) to obtain the pore area and total area of the test area, where porosity = pore area / total area × 100%, and the porosity of different test areas was calculated.
[0095] In some embodiments, compared with the outer shell, the inner core is porous and loose, while the outer shell is dense, the primary particles in the inner core are loosely stacked, and the primary particles in the outer shell are tightly stacked; the loose stacking of the primary particles in the inner core is beneficial to increasing the porosity of the inner core, allowing the positive electrode material to have more electrochemical reaction sites during the charge and discharge cycle, and the tightly stacked arrangement of the primary particles in the outer shell is beneficial to reducing the specific surface area of the positive electrode material, improving the anti-crushing performance of the positive electrode material, and ensuring that the cycle performance and electrochemical capacity of the battery are effectively balanced.
[0096] In some embodiments, the overall porosity of the secondary particles is 0.5-4.0%. The secondary particles have a lower overall porosity and a dense overall structure, which is beneficial to improving the stability of the positive electrode material and promoting an effective balance between the cycle performance and electrochemical capacity of the battery.
[0097] In some embodiments, the porosity of the inner core is 2-10%, and the porosity of the outer shell is 0.01-1%. The inner core has a higher porosity than the outer shell, so that the positive electrode material can have more electrochemical reaction sites during the charge and discharge cycle. The lower porosity of the outer shell is beneficial to reducing the specific surface area of the positive electrode material, thereby improving the anti-crushing performance of the positive electrode material, and promoting an effective balance between the cycle performance and electrochemical capacity of the battery.
[0098] In some embodiments, the cathode material precursor is a nickel-containing hydroxide, for example, nickel-cobalt-manganese hydroxide, nickel-cobalt-manganese-aluminum hydroxide or nickel-cobalt-aluminum hydroxide, etc. In the nickel-containing hydroxide, the introduction of nickel element is beneficial to improve the electrochemical performance of the cathode material, promote the battery to have a higher energy density, and thus effectively balance the cycle performance and electrochemical capacity.
[0099] In some embodiments, the molar content of nickel accounts for 50-70% of the molar content of total metal elements. For example, the molar content of nickel accounts for 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% or any percentage in the range of 50-70%.
[0100] It should be clear that in the prior art, the positive electrode material prepared by using the transition metal hydroxide in which the nickel molar content accounts for more than 80% of the total metal molar content as the positive electrode material precursor is a high-nickel positive electrode material, which has excellent electrochemical properties but poor anti-crushing properties, while the positive electrode material prepared by using the transition metal hydroxide in which the nickel molar content accounts for less than 40% of the total metal element molar content as the positive electrode material precursor is a low-nickel positive electrode material, which has good anti-crushing properties but poor electrochemical properties. The molar content of nickel accounts for 40% to 80% of the total metal element molar content, which belongs to the medium-nickel positive electrode material, which has good anti-crushing properties but has the same defects as the low-nickel positive electrode material, that is, poor electrochemical properties, and the electrochemical capacity of the manufactured battery is not good.
[0101] The molar content of nickel in the positive electrode material precursor of the present application accounts for 50-70% of the molar content of the total metal elements, and the prepared positive electrode material is a medium-nickel positive electrode material. Combined with the morphology optimization design of the positive electrode material precursor, the positive electrode material prepared from the positive electrode material precursor of the present application can have higher thermal stability than the high-nickel positive electrode material in the prior art, and the structure is more stable during the charge and discharge cycle. Compared with the low-nickel positive electrode material and the medium-nickel positive electrode material in the traditional technology, the electrochemical performance is better, and the electrochemical capacity of the prepared battery is higher, which is conducive to achieving an effective balance between the cycle performance and electrochemical capacity of the battery.
[0102] It should be noted that the percentage of the molar content of nickel in the positive electrode material precursor provided in the embodiment of the present application to the total molar content of metals is 50-70%, which means that the ratio of the molar content of nickel element to the molar content of all metal elements in the positive electrode material precursor is converted into a percentage of 50-70%. Specifically, in the positive electrode material precursor of the embodiment of the present application, the content of nickel is between 50% and 70% of the total molar content of the total metal elements (including nickel, cobalt, manganese and other metal elements that may exist).
[0103] In some embodiments, the positive electrode material precursor is a hydroxide containing nickel, cobalt and manganese, for example, nickel, cobalt and manganese hydroxide, nickel, cobalt and manganese aluminum hydroxide, nickel, cobalt and manganese and doped metal hydroxide, etc. Among them, the molar content of manganese accounts for 10-30% of the molar content of the total metal elements, and the molar content of manganese accounts for a relatively high proportion, which is conducive to the preparation of high-voltage positive electrode materials. The positive electrode material has a higher sphericity under the condition of high manganese, which can promote the stability of the positive electrode material under high voltage to inhibit the internal structure changes caused by the insertion / deinsertion of lithium ions during the charge and discharge cycle, effectively reduce the operating power consumption of the battery and improve the safety of the battery.
[0104] It can be understood that the positive electrode material precursor in the embodiment of the present application can be doped nickel cobalt manganese hydroxide or undoped nickel cobalt manganese hydroxide.
[0105] In some embodiments, when the cathode material precursor is doped nickel-cobalt-manganese hydroxide, the chemical formula of the cathode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.5≤x≤0.7, 0.1≤y≤0.3, 0.1≤z≤0.3, 0≤v≤0.015, and M is a doping element; by adjusting the positive electrode material precursors such as Ni, Co, and Mn to be within the proportion range in the above chemical formula, the cycle stability and electrochemical performance of the positive electrode material can be optimized.
[0106] In some embodiments, the chemical formula of the cathode material precursor is Ni x Co y Mn z M v In (OH)2, 0.60<x<0.70, 0.10<y<0.25, 0.15<z<0.25, 0≤v≤0.015, elements such as Ni, Co, and Mn are within the above-mentioned ratio range, which is more conducive to optimizing the cycle stability and electrochemical performance of the positive electrode material.
[0107] In some embodiments, the doping element M may be at least one of Al, Ti, Zr, Mo, Cr, W, Mg, Ba, Nb or Sr. Appropriate doping of the above elements can enhance the crystal structure stability of the positive electrode material, thereby suppressing structural changes during the charge and discharge cycle, thereby improving the cycle performance of the battery.
[0108] It should be understood that, based on the above structural parameters, the cathode material precursor in the embodiment of the present application can be prepared by a co-precipitation method, a sol-gel method or a hydrothermal method. The following is an example of a feasible method for preparing cathode materials.
[0109] In order to prepare the above-mentioned cathode material precursor, another embodiment of the present application provides a method for preparing the cathode material precursor, comprising:
[0110] Preparing a metal salt solution, a precipitant solution and a complexing agent solution, and mixing the solvent, the precipitant solution and the complexing agent solution to obtain a base solution;
[0111] A metal salt solution, a precipitant solution and a complexing agent solution are introduced into the base liquid to perform a synthesis reaction in stages to obtain a hydroxide slurry;
[0112] After post-processing the hydroxide slurry, a positive electrode material precursor is obtained.
[0113] It should be noted that the embodiment of the present application adopts a multi-stage coprecipitation synthesis reaction to prepare the positive electrode material precursor, so as to facilitate the fine control of various reaction parameters in the reaction process, realize the targeted regulation of the morphology of the positive electrode material precursor, and then obtain the positive electrode material precursor particle size D50 and the primary particle volume mean V on the secondary particle surface to satisfy the relationship: (D50) 3 / V=600~1400 positive electrode material precursor.
[0114] In some embodiments, the synthesis reaction includes a first synthesis stage, a second synthesis stage and a third synthesis stage which are performed sequentially, wherein:
[0115] In the first synthesis stage, the pH value of the reaction system is maintained unchanged during the first period of time after the synthesis reaction begins;
[0116] In the second synthesis stage, the pH value of the reaction system is controlled to drop to the first target pH value within the second time period, and then the reaction is continued for a third time period;
[0117] In the third synthesis stage, the pH value of the reaction system is controlled to remain unchanged, or to increase or decrease to the second target pH value within a fourth time period; and, in the third synthesis stage, the concentration of the complexing agent in the reaction system is controlled to remain unchanged, or to increase or decrease to the target concentration value within a fifth time period, and the reaction continues; hydroxide slurry is obtained; wherein, the reaction time of the third synthesis stage is greater than the reaction time of the second synthesis stage, and the reaction time of the second synthesis stage is greater than the reaction time of the first synthesis stage.
[0118] In the above preparation method, the first synthesis stage can preliminarily form seed crystals of the positive electrode material precursor; the second synthesis stage can further grow crystals based on the already formed seed crystals, and by controlling the pH value of the reaction system to drop to the first target pH value within the second time period, the particle size distribution and morphology of the inner core can be controlled to make it more uniform and regular; the inner core obtained in the second synthesis stage continues to undergo the reaction in the third synthesis stage to further grow the outer shell of the secondary particles, and by adjusting and controlling the pH value of the reaction system and the concentration of the complexing agent, the particle size distribution and outer shell morphology of the secondary particles can be controlled to obtain a hydroxide slurry that meets the morphological conditions, and the positive electrode material precursor can be obtained after post-treatment of the hydroxide slurry. It should be understood that the pH value adjustment and complexing agent concentration adjustment of the reaction system during the reaction process are intended to control the primary particle size to produce a cathode material precursor with a target morphology; for example, in the second synthesis stage, after the pH value of the reaction system is controlled to drop to the first target pH value within the second time period, the primary particle size of the inner core is reduced accordingly; in the third synthesis stage, after the pH value of the reaction system rises or drops to the second target pH value within the fourth time period, the primary particle size of the outer shell is increased or decreased accordingly, and after the complexing agent of the reaction system is controlled to rise or drop to the target concentration value within the fifth time period, the primary particle size of the outer shell is also increased or decreased accordingly. The pH value and complexing agent concentration are controlled at each synthesis stage to facilitate the stable production of a cathode material precursor with a morphology that meets the relationship (D50) that the particle size D50 of the cathode material precursor and the primary particle volume mean V on the surface of the secondary particles satisfy the relationship (D50) 3 / V=600~1400 positive electrode material precursor.
[0119] In some embodiments, post-processing includes washing, centrifuging, drying, and sieving and demagnetizing the hydroxide slurry in sequence; washing, centrifuging, drying, and sieving and demagnetizing the hydroxide slurry in sequence helps to remove impurities and volatile solvents, making the positive electrode material precursor more pure and the particle size distribution more uniform.
[0120] In some embodiments, the synthesis reaction is carried out in a reactor, and before the third synthesis stage, the material after the reaction in the second synthesis stage is separated into separate reactors. The separation operation is beneficial to reducing the specific surface area of the positive electrode material and improving the sphericity of the positive electrode material precursor.
[0121] In some embodiments, when the pH value of the reaction system is controlled to decrease during the second time period, the pH value of the reaction system decreases by 0.10 to 0.20 every 1 to 2 hours; optionally, when the pH value of the reaction system is controlled to increase or decrease during the fourth time period, the pH value of the reaction system increases or decreases by 0.10 to 0.20 every 1 to 2 hours.
[0122] Furthermore, when the concentration of the complexing agent in the reaction system is controlled to increase or decrease within the fifth time period, the concentration of the complexing agent in the reaction system increases or decreases by 0.4 to 0.6 g / L correspondingly every 1 to 2 hours.
[0123] Furthermore, the first target pH value is 11.20-11.60.
[0124] Further, when the pH value of the reaction system is controlled to increase in the fourth time period, the second target pH value is 11.00-11.40; or, when the pH value of the reaction system is controlled to decrease in the fourth time period, the second target pH value is 11.40-11.80.
[0125] Further, when the complexing agent concentration of the reaction system is controlled to increase in the fifth time period, the target concentration value is 5.0g / L to 7.5g / L; or, when the complexing agent concentration of the reaction system is controlled to decrease in the fifth time period, the target concentration value is 7.5g / L to 9.0g / L.
[0126] It should be noted that in the preparation method of the embodiment of the present application, the pH value of the reaction system and the concentration of the complexing agent have different effects on the morphology and structure of the secondary particles of the cathode material precursor obtained. Within the above range, it is beneficial to promote the cathode material precursor particle size D50 and the primary particle volume mean V on the secondary particle surface to satisfy the relationship: (D50) 3 / V=600~1400, which improves the stability of the positive electrode material and effectively balances the battery's cycle performance and electrochemical capacity.
[0127] In some embodiments, the first time period is 1 to 2 hours; optionally, the second time period or the fourth time period is 4 to 12 hours; optionally, the third time period is 25 to 30 hours; optionally, the fifth time period is 4 to 8 hours; and the total reaction time of the synthesis reaction is 70 to 130 hours.
[0128] In some embodiments, during the synthesis reaction, the feed rate of the metal salt solution is 4-6% / h of the reaction container volume; during the synthesis reaction, the feed rate of the precipitant solution is 1.5-3.5% / h of the reaction container volume; during the synthesis reaction, the feed rate of the complexing agent solution is 0.20-0.60% / h of the reaction container volume.
[0129] In some embodiments, the reaction temperature of the synthesis reaction is 40-60°C, preferably 45-55°C.
[0130] In some embodiments, the first synthesis reaction and the second synthesis reaction are both performed under a protective atmosphere, and the protective atmosphere may be an inert gas.
[0131] In some embodiments, the total metal molar amount of the metal salt solution is 1.5-2.5 mol / L; the solute mass fraction of the precipitant solution is 30-34 wt %; and the solute mass fraction of the complexing agent solution is 20-26 wt %.
[0132] In some embodiments, the pH value of the base solution is 11.60-12.00; the concentration of the complexing agent in the base solution is 6.4-8.0 g / L.
[0133] In some embodiments, the nickel-containing metal salt solution includes a salt solution containing Ni and at least one metal element of Co, Mn, and M, where M is at least one of Al, Ti, Zr, Mo, Cr, W, Mg, Ba, Nb, and Sr.
[0134] In some embodiments, the precipitant solution includes sodium hydroxide solution; the complexing agent solution includes aqueous ammonia; the solvent includes pure water; and pure water refers to H2O without impurities.
[0135] Another embodiment of the present application further provides a positive electrode material, wherein the raw material of the positive electrode material includes the positive electrode material precursor as described above or the positive electrode material precursor prepared by the preparation method.
[0136] Another embodiment of the present application further provides a battery, which includes an electrode made of the positive electrode material as described above.
[0137] Another embodiment of the present application further provides an electrical device, comprising the battery as described above.
[0138] The following examples describe the disclosure of the present application in more detail, and these examples are merely illustrative, as it will be apparent to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all reagents and raw materials used in the examples are commercially available or synthesized according to conventional methods, and the instruments used in the examples are commercially available.
[0139] Example 1
[0140] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0141] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0142] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours in the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage is carried out. After the start of the second synthesis stage, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage.
[0143] The total volume of the split reactor is 1 / 2 of the intermediate slurry. After the split reactor operation is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the reaction endpoint of the second synthesis stage. The original feed rate is maintained to introduce nickel metal salt, sodium hydroxide solution, ammonia water and inert gas into the reactor again, and the pH of the reaction system is controlled to be maintained at 11.40, and the ammonia concentration is maintained at 7.5g / L to carry out the third synthesis stage reaction. The clearance rate during the reaction of the third synthesis stage is consistent with the total feed amount. After the total reaction time is as long as 108h, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.05μm is obtained; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.05μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0144] Example 2
[0145] Provide a positive electrode material precursor Ni 0.600 Co0.200 Mn 0.200 (OH)2, the preparation process includes:
[0146] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0147] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours in the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage is carried out. After the start of the second synthesis stage, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage.
[0148] The total volume of the split reactor is 1 / 2 of the intermediate slurry. After the split reactor operation is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the reaction endpoint of the second synthesis stage. The original feed rate is maintained to introduce nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas into the reactor again, and the pH of the reaction system is controlled to be maintained at 11.40, and the ammonia concentration is maintained at 7.5g / L to carry out the third synthesis stage reaction. The clearance rate during the reaction of the third synthesis stage is consistent with the total feed amount. After the total reaction time is as long as 84h, a nickel-cobalt-manganese hydroxide slurry with a particle size D50 of 6.04μm is obtained; the nickel-cobalt-manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 6.04μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0149] Example 3
[0150] Provide a positive electrode material precursor Ni 0.595 Co 0.200 Mn 0.200 Al 0.005 (OH)2, the preparation process includes:
[0151] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals, manganese sulfate salt crystals and aluminum sulfate salt crystals in a ratio of Ni: Co: Mn: Al = 59.5: 20: 20: 0.5, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0152] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours in the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage is carried out. After the start of the second synthesis stage, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage.
[0153] The total volume of the split reactor is 1 / 2 of the intermediate slurry. After the split reactor operation is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the reaction endpoint of the second synthesis stage. The original feed rate is maintained to introduce nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas into the reactor again, and the pH of the reaction system is controlled to be maintained at 11.40, and the ammonia concentration is maintained at 7.5g / L to carry out the third synthesis stage reaction. The clearance rate during the reaction of the third synthesis stage is consistent with the total feed amount. After the total reaction time is as long as 115h, an aluminum-doped nickel-cobalt-manganese hydroxide slurry with a particle size D50 of 7.09μm is obtained; the aluminum-doped nickel-cobalt-manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.09μm. 0.595 Co 0.200 Mn 0.200 Al 0.005 (OH)2.
[0154] Example 4
[0155] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0156] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0157] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the second synthesis stage reaction begins, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage reactions.
[0158] After the split-tank reactor is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the end point of the second synthesis stage reaction. The nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas are introduced into the reactor again at the original feed rate to carry out the third synthesis stage reaction. After the start of the third synthesis stage reaction, the pH of the reaction system is controlled to increase by 0.1 every 2 hours. After 4 hours of increase, the pH of the reaction system is maintained at 11.60, and after the start of the third synthesis stage reaction, the pH of the reaction system is controlled to increase by 0.1 every 2 hours. After the increase, the pH of the reaction system is maintained at 11.60. The ammonia concentration of the reaction system was increased by 0.5 g / L every 2 hours, that is, the flow rate of ammonia water was adjusted to maintain it at 9.0 g / L after it increased for 6 hours. At this time, the reaction entered a stable period and continued. The clearance rate during the reaction of the third synthesis stage was consistent with the total feed amount. The reaction was continued until the total reaction time was as long as 109 hours, and a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.11 μm was obtained. The nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.11 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0159] Example 5
[0160] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0161] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0162] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the second synthesis stage reaction begins, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage reactions.
[0163] After the split-tank reactor is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the end point of the second synthesis stage reaction. The nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas are introduced into the reactor again at the original feed rate to carry out the third synthesis stage reaction. After the start of the third synthesis stage reaction, the pH of the reaction system is controlled to decrease by 0.1 every 2 hours. After decreasing for 4 hours, the pH of the reaction system is maintained at 11.20, and after the start of the third synthesis stage reaction, the pH of the reaction system is controlled to decrease by 0.1 every 2 hours. After decreasing for 4 hours, the pH of the reaction system is maintained at 11.20. The ammonia concentration of the reaction system was reduced by 0.5 g / L every 2 hours, that is, the flow rate of ammonia water was adjusted to maintain it at 6.0 g / L after it was reduced for 6 hours. At this time, the reaction entered a stable period and continued. The clearance rate during the reaction of the third synthesis stage was consistent with the total feed amount. The reaction was continued until the total reaction time was as long as 107 hours, and a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.09 μm was obtained. The nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.09 μm. 0.600 Co 0.200 Mn 0.200(OH)2.
[0164] Example 6
[0165] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0166] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0167] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the second synthesis stage reaction begins, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage reactions.
[0168] After the split-tank reactor is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the end point of the second synthesis stage reaction. The nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas are introduced into the reactor again at the original feed rate to carry out the third synthesis stage reaction. After the start of the third synthesis stage reaction, the pH of the reaction system is controlled to increase by 0.1 every 2 hours. After 4 hours of increase, the pH of the reaction system is maintained at 11.60, and after the start of the third synthesis stage reaction, the pH of the reaction system is controlled to increase by 0.1 every 2 hours. After the increase, the pH of the reaction system is maintained at 11.60. The ammonia concentration of the reaction system was reduced by 0.5 g / L every 2 hours, that is, the flow rate of ammonia water was adjusted to maintain it at 6.0 g / L after it was reduced for 6 hours. At this time, the reaction entered a stable period and continued. The clearance rate during the reaction of the third synthesis stage was consistent with the total feed amount. The reaction was continued until the total reaction time was as long as 104 hours, and a nickel cobalt manganese hydroxide slurry with a particle size D50 of 6.97 μm was obtained. The nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 6.97 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0169] Example 7
[0170] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0171] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0172] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the second synthesis stage reaction begins, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage reactions.
[0173] After the split-tank reactor is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the end point of the second synthesis stage reaction. The nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas are introduced into the reactor again at the original feed rate to carry out the third synthesis stage reaction. After the start of the third synthesis stage reaction, the pH of the reaction system is controlled to decrease by 0.1 every 2 hours. After decreasing for 4 hours, the pH of the reaction system is maintained at 11.20, and after the start of the third synthesis stage reaction, the pH of the reaction system is controlled to decrease by 0.1 every 2 hours. After decreasing for 4 hours, the pH of the reaction system is maintained at 11.20. The ammonia concentration of the reaction system was reduced by 0.5 g / L every 2 hours, that is, the flow rate of ammonia water was adjusted to increase it for 6 hours and then maintain at 9.0 g / L. At this time, the reaction entered a stable period and continued. The clearance rate during the reaction of the third synthesis stage was consistent with the total feed amount. The reaction was continued until the total reaction time was as long as 119 hours, and a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.59 μm was obtained. The nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.59 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0174] Example 8
[0175] Provide a positive electrode material precursor Ni 0.500 Co 0.250 Mn 0.250 (OH)2, the preparation process includes:
[0176] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=50:25:25, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0177] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the second synthesis stage reaction begins, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage reactions.
[0178] The total volume of the split reactor is 1 / 2 of the intermediate slurry. After the split reactor operation is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the reaction endpoint of the second synthesis stage. The original feed rate is maintained and the nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas are introduced into the reactor again to carry out the third synthesis stage reaction. After the reaction of the third synthesis stage begins, the pH of the reaction system is controlled to be 11.40 and the ammonia concentration is maintained at 7.5g / L. At this time, the stable period continues to react. The clearance rate during the reaction of the third synthesis stage is consistent with the total feed amount. The reaction is continued until the total reaction time is as long as 101h to obtain a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.11μm; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.11μm. 0.500 Co 0.250 Mn 0.250 (OH)2.
[0179] Example 9
[0180] Provide a positive electrode material precursor Ni 0.700 Co 0.150 Mn 0.150 (OH)2, the preparation process includes:
[0181] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=70:15:15, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 15L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 250r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.80 and an ammonia concentration of 7.5g / L;
[0182] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.2% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the second synthesis stage reaction begins, the pH value of the reaction system is reduced by 0.1 every 2 hours until it enters a stable period after 8 hours. At this time, the pH value of the reaction system is maintained at 11.40. The reaction is continued for 25 hours to obtain an intermediate slurry with a particle size D50 of 3.5 μm. The ammonia concentration of the reaction system is controlled to be 7.5 g / L during the first synthesis stage and the second synthesis stage reactions.
[0183] The total volume of the split reactor is 1 / 2 of the intermediate slurry. After the split reactor operation is completed, the pH and ammonia concentration of the reaction system are recalibrated to the same conditions as the reaction endpoint of the second synthesis stage. The original feed rate is maintained and the nickel-containing metal salt, sodium hydroxide solution, ammonia water and inert gas are introduced into the reactor again to carry out the third synthesis stage reaction. After the reaction of the third synthesis stage begins, the pH of the reaction system is controlled to be 11.40 and the ammonia concentration is maintained at 7.5g / L. At this time, the stable period continues to react. The clearance rate during the reaction of the third synthesis stage is consistent with the total feed amount. The reaction is continued until the total reaction time is as long as 114h to obtain a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.05μm; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.05μm. 0.70 Co0.15 Mn 0.15 (OH)2.
[0184] Comparative Example 1
[0185] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0186] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 28L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 12.10 and an ammonia concentration of 7.5g / L;
[0187] Keeping the inert gas introduction conditions unchanged, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water were simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.28% / h, respectively, based on the volume of the reactor. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction was carried out in stages. After the first synthesis stage began, the mother liquor was discharged through a concentration and solidification device. The clearing flow rate was the same as the feed flow rate, and the clearing rate was consistent with the total feed amount. The pH value of the reaction system was maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacted for 2 hours, the reaction was carried out. In the second synthesis stage, after the start of the second synthesis stage, the pH value of the reaction system is reduced by 0.1 every 2 hours until the pH value of the reaction system is maintained at 11.50 after 12 hours, and the ammonia concentration is maintained at 7.5 g / L. At this time, the reaction enters the stable period and continues. The clearance rate during the reaction is consistent with the total feed amount. After the total reaction time is as long as 65 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 4.02 μm is obtained; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 4.02 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0188] Comparative Example 2
[0189] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200(OH)2, the preparation process includes:
[0190] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 8L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.50 and an ammonia concentration of 7.5g / L;
[0191] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel metal salt solution, sodium hydroxide solution, and ammonia water were simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction was carried out in stages. After the first synthesis stage began, the mother liquor was discharged through a concentration and solidification device. The clearing flow rate was the same as the feed flow rate, and the clearing rate was consistent with the total feed amount. The pH value of the reaction system was maintained unchanged for 2 hours before the first synthesis stage. After the first stage reaction for 2 hours, the second synthesis stage reaction was carried out. After the second synthesis stage reaction started, the pH value of the reaction system was maintained at 11.50, and the ammonia concentration was maintained at 7.5 g / L. At this time, the reaction entered the stable period and continued. The clearance rate during the reaction was consistent with the total feed amount. After the total reaction time was as long as 109 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 9.07 μm was obtained; the nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 4.02 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0192] Comparative Example 3
[0193] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0194] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 6L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.20 and an ammonia concentration of 7.5g / L;
[0195] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis is carried out. The reaction was carried out in stages. After the reaction of the second synthesis stage started, the pH value of the reaction system was reduced by 0.1 every 1 hour until the pH value of the reaction system was maintained at 10.50 after 12 hours, and the ammonia concentration was maintained at 7.5 g / L. At this time, the reaction entered a stable period and continued. The clearance rate during the reaction was consistent with the total feed amount. After the total reaction time was as long as 72 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.08 μm was obtained. The nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.08 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0196] Comparative Example 4
[0197] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0198] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 8L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.50 and an ammonia concentration of 7.5g / L;
[0199] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, the sodium hydroxide solution, and the ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through the concentration and solidification equipment. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the reaction of the second synthesis stage begins, the reaction system is discharged every 2 hours. The pH value of the system is increased by 0.1, until the pH value of the reaction system is maintained at 11.70 after 4 hours, and after the reaction of the second synthesis stage starts, the ammonia concentration of the reaction system is increased by 1 g / L every 2 hours by adjusting the flow rate of ammonia water, until the ammonia concentration of the reaction system is maintained at 11 g / L after 7.5 hours, and then the reaction enters a stable period and continues. The clearance rate during the reaction is consistent with the total feed amount. After the total reaction time is as long as 106 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.06 μm is obtained; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.06 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0200] Example 10
[0201] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0202] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 8L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.50 and an ammonia concentration of 7.5g / L;
[0203] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, nickel metal salt solution, sodium hydroxide solution and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the start of the first synthesis stage, the mother liquor is discharged through the concentration and solidification equipment. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage has reacted for 2 hours, the second synthesis stage reaction is carried out. After the start of the second synthesis stage reaction, the mother liquor is discharged every 2 hours. The pH value of the reaction system is increased by 0.1, until the pH value of the reaction system is maintained at 11.70 after 4 hours, and after the reaction of the second synthesis stage starts, the ammonia concentration of the reaction system is reduced by 1g / L every 2 hours by adjusting the flow rate of ammonia water, until the ammonia concentration of the reaction system is maintained at 4g / L after 7 hours, then the reaction enters a stable period and continues, and the clearance rate during the reaction is consistent with the total feed amount. After the total reaction time is as long as 104 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.04μm is obtained; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.04μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0204] Embodiment 11
[0205] Provide a positive electrode material precursor Ni 0.600 Co 0.200 Mn 0.200 (OH)2, the preparation process includes:
[0206] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=60:20:20, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 8L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.50 and an ammonia concentration of 7.5g / L;
[0207] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, the sodium hydroxide solution, and the ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through the concentration and solidification equipment. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reaction is carried out. After the reaction of the second synthesis stage begins, the reaction system is discharged every 1 hour. The pH value of the system is reduced by 0.1, until the pH value of the reaction system is maintained at 10.50 after 10 hours, and after the reaction of the second synthesis stage starts, the ammonia concentration of the reaction system is increased by 1 g / L every 2 hours by adjusting the flow rate of ammonia water, until the ammonia concentration of the reaction system is maintained at 13 g / L after 11 hours, then the reaction enters a stable period, and the clearance rate during the reaction is consistent with the total feed amount. After the total reaction time is as long as 106 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.06 μm is obtained; the nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.06 μm. 0.600 Co 0.200 Mn 0.200 (OH)2.
[0208] Comparative Example 5
[0209] This embodiment provides a positive electrode material precursor Ni 0.400 Co 0.300 Mn 0.300 (OH)2, the preparation process includes:
[0210] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=40:30:30, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 9.5L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.60 and an ammonia concentration of 7.5g / L;
[0211] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel-containing metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h, and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the first synthesis stage begins, the mother liquor is discharged through a concentration and solidification device. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained unchanged for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis is carried out. The reaction was carried out in stages, and the pH value of the reaction system was reduced by 0.1 every 1 h after the start of the second synthesis stage reaction, until the pH value of the reaction system was maintained at 11.40 after 4 h, and the ammonia concentration was maintained at 7.5 g / L after the start of the second synthesis stage reaction. The clearance rate during the reaction was consistent with the total feed amount. After the total reaction time was as long as 106 h, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.01 μm was obtained; the nickel cobalt manganese hydroxide slurry was washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.01 μm. 0.400 Co 0.300 Mn 0.300 (OH)2.
[0212] Comparative Example 6
[0213] Provide a positive electrode material precursor Ni 0.800 Co 0.100 Mn 0.100 (OH)2, the preparation process includes:
[0214] Weigh nickel sulfate salt crystals, cobalt sulfate salt crystals and manganese sulfate salt crystals in a ratio of Ni:Co:Mn=80:10:10, and prepare a nickel-containing metal salt solution with a total metal molar amount of 2 mol / L, prepare a sodium hydroxide solution with a solute mass fraction of 32wt% and an ammonia solution with a solute mass fraction of 23wt%; introduce an inert gas into the reactor to exhaust air (the inert gas introduction pressure is 0.2Mpa, the introduction rate is 1000L / h, and the introduction time is 2h), add 6000L of pure water, 6.5L of the prepared sodium hydroxide solution and 160L of ammonia solution into the reactor, and stir at 260r / min for 1h until uniform, and control the temperature to a constant temperature of 50°C to obtain a bottom solution with a pH value of 11.40 and an ammonia concentration of 7.5g / L;
[0215] Keeping the inert gas introduction conditions unchanged, based on the volume of the reactor, the nickel metal salt solution, sodium hydroxide solution and ammonia water are simultaneously introduced into the reactor at feed rates of 5.5% / h, 2.5% / h and 0.28% / h, respectively. Under the condition of a constant reaction temperature of 50°C, the synthesis reaction is carried out in stages. After the start of the first synthesis stage, the mother liquor is discharged through the concentration and solidification equipment. The clearing flow rate is the same as the feed flow rate, and the clearing rate is consistent with the total feed amount. The pH value of the reaction system is maintained constant for 2 hours before the first synthesis stage. After the first synthesis stage reacts for 2 hours, the second synthesis stage reacts. After the second synthesis stage reaction starts, the pH value of the reaction system is maintained at 11.40 and the ammonia concentration is maintained at 7.5 g / L. The clearing rate during the reaction is consistent with the total feed amount. After the total reaction time is as long as 105 hours, a nickel cobalt manganese hydroxide slurry with a particle size D50 of 7.04 μm is obtained. The nickel cobalt manganese hydroxide slurry is washed, centrifuged, dried, sieved and demagnetized to obtain a positive electrode material precursor Ni with a particle size D50 of 7.04 μm. 0.800 Co 0.100 Mn 0.100 (OH)2.
[0216] Physical and chemical analysis
[0217] The positive electrode material precursors prepared in each embodiment and comparative example were characterized and tested. The physical and chemical data obtained from the tests are as follows: Figures 1 to 6 As shown in Table 1 and Table 2 below, Figure 1 This is a SEM image of the positive electrode material precursor prepared in Example 1 of the present application (magnification 10000 times); Figure 2 CP diagram of the cathode material precursor prepared in Example 1 of the present application (magnification 10000 times); Figure 3 This is a SEM image of the cathode material precursor prepared in Example 1 of the present application (magnification 200 times on the left, magnification 1000 times on the right); Figure 4 This is a SEM image of the positive electrode material precursor prepared in Example 1 of the present application (the magnification of the left and right sides is 50,000 times); Figure 5This is a SEM image of the cathode material precursor prepared in Example 2 of the present application (magnification 10000 times); Figure 6 This is a SEM image of the positive electrode material precursor prepared in Comparative Example 1 of the present application (magnification 10,000 times).
[0218] Table 1. Statistical table of physical and chemical data of cathode material precursors
[0219]
[0220]
[0221] Table 2. Statistical table of physical and chemical data of cathode material precursors
[0222]
[0223]
[0224] It should be noted that the calculation formula for the secondary particle breakage rate in Table 2 above is: particle breakage rate = ΔDv3 / Dv3.
[0225] The secondary particle breakage rate test method is as follows: before the test, the particle size Dv3 of the test sample is tested and recorded, about 1g of the sample is weighed, and placed in the mold of a microcomputer electronic pressure testing machine (mold shape: a cylinder with a diameter of 13mm) for testing, and the applied pressure is set to 0.75T. When the pressure rises to the set value of 0.75T, the material is taken out to test the particle size Dv3' and record it; wherein, Dv3 refers to the particle size value of the precursor secondary particle sample when the cumulative volume distribution is 3% before the particle breakage rate test; Dv3' refers to the particle size value of the precursor secondary particle sample when the cumulative volume distribution is 3% after the particle breakage rate test; ΔDv3 is the change in particle size before and after the cumulative volume distribution of the precursor secondary particle sample is 3% under a pressure of 0.75T and a circular cross-section of 13mm, and the calculation formula is: ΔDv3=Dv3-Dv3'. The lower the ΔDv3 / Dv3 ratio is, the smaller the change in particle size of the secondary particles under the action of external force is, indicating that the secondary particles are more resistant to crushing.
[0226] Secondly, the average length / width / thickness of the primary particles on the secondary particle surface in Table 2 is measured by taking the cathode material precursor prepared in Example 1 as an example. Figure 4) randomly select multiple primary particles (for example, 20, selected from 4 different secondary particles), measure the edges of each primary particle respectively, obtain the length, width and thickness of a single particle, and average the parameters obtained by combining the multiple primary particles to obtain the average length / width / thickness of the primary particles on the surface of the secondary particles; in addition, the primary particle volume mean V on the secondary particle surface in Table 1 above can be calculated by the length, width and thickness of a single particle obtained as above to obtain the volume parameters of each primary particle, and then the average value is calculated by combining the multiple primary particles to obtain the primary particle volume mean V on the secondary particle surface.
[0227] refer to Figure 1 and Figure 5 It can be found that the primary particles on the surface of the secondary particles of the positive electrode material precursor prepared in Examples 1 and 2 of the present application are relatively thick and block-shaped or long strip-shaped, the primary particles are evenly distributed on the surface of the secondary particles, and the primary particles on the surface of the secondary particles have a large volume and a small number; further reference Figure 2 It can be found that the secondary particles of the positive electrode material precursor of Example 1 include a core-shell structure composed of a core and an outer shell. Compared with the outer shell, the primary particles of the core are loosely stacked, the primary particles in the outer shell are tightly stacked, the core of the secondary particles is porous and loose, and the outer shell is dense. Figure 3 It can be seen that the secondary particles of the positive electrode material precursor in Example 1 have a high sphericity (estimated sphericity R is 90%). Figure 4 It can be seen that the primary particles of the positive electrode material precursor of Example 1 are composed of a plurality of thin sheet units stacked and arranged along the thickness direction.
[0228] In contrast, comparative example 1, reference Figure 6 It can be found that the primary particles of the positive electrode material precursor prepared in Comparative Example 1 are band-shaped, the primary particles are unevenly distributed on the surface of the secondary particles, the primary particles on the surface of the secondary particles are small in volume and small in number, and the secondary particles formed have poor sphericity (estimated sphericity R is about 65%).
[0229] In order to verify the performance advantages of the positive electrode material precursors obtained in each embodiment and comparative example, the positive electrode material precursors obtained in each embodiment and comparative example were used to prepare positive electrode materials. The preparation process of each positive electrode material is as follows:
[0230] 2 kg of the positive electrode material precursor prepared in each embodiment and comparative example was weighed respectively, and the weighed positive electrode material precursor was mixed with LiOH in a molar ratio of 1:1.03 by a high-speed mixer, and sintered in a box furnace under air atmosphere. The sintering temperature was 780°C and the high-temperature sintering time was 12 h. After the sintering operation, it was cooled to room temperature and then crushed and sieved to obtain the positive electrode material.
[0231] The positive electrode material precursors of each embodiment and comparative example were further used to prepare positive electrode material groups to form button-type half-cells for electrochemical performance testing. The preparation process of the button-type half-cells is as follows:
[0232] The positive electrode materials prepared by the positive electrode material precursors of the above-mentioned embodiments and comparative examples were respectively mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a ratio of 8:1:1 to form a slurry, which was coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). In a vacuum glove box, the battery case, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into a button-type half-cell.
[0233] The electrochemical performance of each button-type half-cell was tested using a blue electric test system, the voltage range of the test was 2 to 4.3 V, the current density was 1C = 210 mAh / g, and the test results are shown in Table 3 below;
[0234] Table 3. Electrochemical test data statistics
[0235]
[0236] Referring to Tables 1 to 3, the positive electrode material precursors prepared in Examples 1 to 11 of the present application are hydroxides containing nickel, cobalt and manganese, and the particle size D50 of the positive electrode material precursor and the primary particle volume mean V on the secondary particle surface satisfy the relationship: (D50) 3 / V=600~1400. Compared with comparative examples 1 to 6, the volume of primary particles on the surface of the secondary particles of the positive electrode material precursor of each embodiment is moderate, and the number of primary particles is moderate under the condition of the same secondary particle size, which is beneficial to reduce the secondary particle breakage rate. At the same time, the battery can have both high electrochemical capacity and cycle performance during the charge and discharge cycle.
[0237] Specifically, compared with Example 1, Comparative Examples 1 and 2 have the same chemical formula as Example 1. It can be seen from Tables 1 and 2 that the ratio of the cube of the particle size D50 of the positive electrode material precursors of Comparative Examples 1 and 2 to the primary particle volume mean V on the secondary particle surface is not in the range of 600 to 1400, and the secondary particle breakage rate is more than 6.59%, which is much larger than Example 1. The structural stability of the positive electrode material is poor. Combined with Table 3, the electrochemical test data of the positive electrode materials made from the precursors of Comparative Examples 1 and 2 are lower than those of Example 1, and the electrochemical capacity and cycle performance of the battery are poor.
[0238] In addition, the data of Examples 1, 10 and 11 of the present application verify that the number of thin-sheet units in the positive electrode material precursor needs to be maintained within an appropriate range.
[0239] Compared with Example 1, by doping an appropriate amount of metal element Al, the battery can still maintain a relatively high electrochemical capacity and cycle performance.
[0240] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0241] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A cathode material precursor, characterized in that: The positive electrode material precursor is a hydroxide containing a transition metal; The positive electrode material precursor includes secondary particles composed of a plurality of primary particles, and the particle size D50 of the positive electrode material precursor and the primary particle volume mean V on the surface of the secondary particles satisfy the relationship: (D50) 3 / V=600~1400.
2. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: (1) (D50) 3 / V=800~1200; (2) The particle size D50 of the positive electrode material precursor is 5.00 to 8.00 μm, preferably 6.00 to 7.00 μm; (3) The primary particle volume average V on the secondary particle surface is 0.250 to 0.550 μm 3 , preferably 0.320~0.450μm 3 ; (4) The primary particle comprises a plurality of thin sheet units, and the number of thin sheet units of a single primary particle is 25 to 60, preferably 40 to 50; (5) The secondary particles include a core-shell structure consisting of a core and an outer shell, and the porosity of the core is greater than the porosity of the outer shell.
3. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: A. The specific surface area BET of the positive electrode material precursor is 1.00 to 5.00 m 2 / g, preferably 1.5 to 3.8 m 2 / g; B. The sphericity R of the secondary particles is 86%≤R<100%; C. The overall porosity of the secondary particles is 0.5-4.0%; D. The plurality of thin sheet units of the primary particles are stacked and arranged in a thickness direction; E. The primary particles are in block or strip shape; F. The average length dimension of the primary particles on the surface of the secondary particles is 0.710 to 0.830 μm; optionally, the average width dimension of the primary particles on the surface of the secondary particles is 0.590 to 0.870 μm; optionally, the average thickness dimension of the primary particles on the surface of the secondary particles is 0.510 to 0.810 μm.
4. The cathode material precursor according to any one of claims 1 to 3, characterized in that: The positive electrode material precursor is a nickel-containing hydroxide and satisfies at least one of the following conditions; ① The molar content of nickel accounts for 50-70% of the molar content of the total metal elements; ②, the positive electrode material precursor is a hydroxide containing nickel, cobalt and manganese, and the molar content of manganese accounts for 10-30% of the molar content of the total metal elements; ③. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.5≤x≤0.7, 0.1≤y≤0.3, 0.1≤z≤0.3, 0≤v≤0.015, and M is a doping element; optionally, 0.60<x<0.70, 0.10<y<0.25, 0.15<z<0.25, 0≤v≤0.015; optionally, M is at least one of Al, Ti, Zr, Mo, Cr, W, Mg, Ba, Nb or Sr.
5. A method for preparing a cathode material precursor according to any one of claims 1 to 4, characterized in that: include: Preparing a metal salt solution, a precipitant solution and a complexing agent solution, and mixing a solvent, the precipitant solution and the complexing agent solution to obtain a base solution; The metal salt solution, the precipitant solution and the complexing agent solution are introduced into the base liquid to perform synthesis reaction in stages to obtain hydroxide slurry; After post-processing the hydroxide slurry, a positive electrode material precursor is obtained.
6. The method for preparing a cathode material precursor according to claim 5, characterized in that: The synthesis reaction comprises a first synthesis stage, a second synthesis stage and a third synthesis stage which are carried out in sequence, wherein: In the first synthesis stage, the pH value of the reaction system is maintained unchanged during the first time period after the synthesis reaction starts; In the second synthesis stage, the pH value of the reaction system is controlled to gradually decrease to the first target pH value within the second time period, and then the reaction is continued for a third time period; In the third synthesis stage, the pH value of the reaction system is controlled to remain unchanged, or to increase or decrease to the second target pH value within the fourth time period and then continue to react; and, in the third synthesis stage, the concentration of the complexing agent in the reaction system is controlled to remain unchanged, or to increase or decrease to the target concentration value within the fifth time period and then continue to react; to obtain a hydroxide slurry; The reaction time of the third synthesis stage is greater than that of the second synthesis stage, and the reaction time of the second synthesis stage is greater than that of the first synthesis stage.
7. The method for preparing a cathode material precursor according to claim 6, characterized in that: The preparation method selects one or more of the following conditions: a. The post-treatment includes washing, centrifuging, drying and screening to remove magnetism of the hydroxide slurry in sequence; b. The synthesis reaction is carried out in a reactor, and before the third synthesis stage, the materials after the reaction in the second synthesis stage are separated into separate reactors; c. When the pH value of the reaction system is controlled to decrease during the second time period, the pH value of the reaction system decreases by 0.10 to 0.20 every 1 to 2 hours; optionally, when the pH value of the reaction system is controlled to increase or decrease during the fourth time period, the pH value of the reaction system increases or decreases by 0.10 to 0.20 every 1 to 2 hours; d. Controlling the concentration of the complexing agent in the reaction system to increase or decrease during the fifth time period, so that the concentration of the complexing agent in the reaction system increases or decreases by 0.4 to 0.6 g / L every 1 to 2 hours; e. The first target pH value is 11.20 to 11.60; f. When the pH value of the reaction system is controlled to rise in the fourth time period, the second target pH value is 11.00 to 11.40; or, when the pH value of the reaction system is controlled to fall in the fourth time period, the second target pH value is 11.40 to 11.80; g. When the concentration of the complexing agent in the reaction system is controlled to increase in the fifth time period, the target concentration value is 5.0 g / L to 7.5 g / L; or, when the concentration of the complexing agent in the reaction system is controlled to decrease in the fifth time period, the target concentration value is 7.5 g / L to 9.0 g / L; h, the first time period is 1 to 2 hours; optionally, the second time period or the fourth time period is 4 to 12 hours; optionally, the third time period is 25 to 30 hours; optionally, the fifth time period is 4 to 8 hours; i. The total reaction time of the synthesis reaction is 70 to 130 hours; j. During the synthesis reaction, the feed rate of the metal salt solution is 4-6% / h of the reaction vessel volume; k. During the synthesis reaction, the feed rate of the precipitant solution is 1.5-3.5% / h of the reaction vessel volume; 1. During the synthesis reaction, the feeding rate of the complexing agent solution is 0.20-0.60% / h of the reaction vessel volume; m. The reaction temperature of the synthesis reaction is 40 to 60°C, preferably 45 to 55°C; n. The total metal molar amount of the metal salt solution is 1.5 to 2.5 mol / L; o. The solute mass fraction of the precipitant solution is 30-34wt%; p. The solute mass fraction of the complexing agent solution is 20 to 26 wt %; q. The pH value of the base solution is 11.60-12.00; r. The complexing agent concentration of the base solution is 6.4-8.0 g / L; s. The precipitant solution comprises a sodium hydroxide solution; t. The complexing agent solution includes aqueous ammonia.
8. A positive electrode material, characterized in that The raw material of the positive electrode material includes the positive electrode material precursor according to any one of claims 1 to 4 or the positive electrode material precursor prepared by the preparation method according to any one of claims 5 to 7.
9. A battery, characterized in that: The battery comprises an electrode made of the positive electrode material as claimed in claim 8.
10. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 9.
Citation Information
Cited By
Wide particle size distribution ternary precursor, method of making and use thereof
CN122540936A